2013
DOI: 10.1038/leu.2013.244
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of whole-body MRI in patients with monoclonal gammopathy of undetermined significance

Abstract: Radiological skeletal survey or computed tomography are currently applied to assess bone diseases in patients with monoclonal plasma cell disorders. Whole-body magnetic resonance imaging (whole-body MRI) allows detecting the infiltration of clonal cells in nearly the whole bone marrow compartment even before bone destruction has occurred. Those MRI results (i.e., patterns of bone marrow infiltration) have been demonstrated to be of prognostic significance in patients with symptomatic as well as asymptomatic mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 32 publications
0
33
0
5
Order By: Relevance
“…A main advantage of MRI cited in the literature is the improved detection of diffuse bone marrow infiltration by myeloma cells (18). MRI allows for imaging of the bone cavity content and can detect changes in marrow density and identify marrow infiltration patterns before development of any bone destruction in patients with MGUS (19,20). Diffuse involvement of the bone marrow by multiple myeloma is better detected by WB-MRI, leading to upstaging in cases where diffuse bone loss could be misinterpreted as senile osteoporosis by WBLDCT (9).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…A main advantage of MRI cited in the literature is the improved detection of diffuse bone marrow infiltration by myeloma cells (18). MRI allows for imaging of the bone cavity content and can detect changes in marrow density and identify marrow infiltration patterns before development of any bone destruction in patients with MGUS (19,20). Diffuse involvement of the bone marrow by multiple myeloma is better detected by WB-MRI, leading to upstaging in cases where diffuse bone loss could be misinterpreted as senile osteoporosis by WBLDCT (9).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…1 Prognostic significance of whole-body MRI, M-protein level and age for the initiation of treatment, overall and progression-free survival has already been published for a part of the patient population (132 of 138 patients classified as MGUS). 20 …”
Section: Patient Populationmentioning
confidence: 99%
“…Some studies comparing WB-MRI and PET/CT showed that whole body MRI has higher sensitivity and specificity over PET/CT, which is more sensitive in the detection of extramedullary plasmocytoma 1,3,4,20,21 . MRI is able to distinguish tumorous and benign structural changes, and even to differentiate incipient MBD in the form of "pepper and salt" involvement from osteoporosis.…”
Section: 2413-16mentioning
confidence: 99%